Caracterização de linhagens de milho e avaliação do controle genético para tolerância ao herbicida mesotrione - Santos, Claudia Maria Prado dos (2017)
The use of herbicides to control weeds in maize is widely used in the conventional Brazilian cultivation system. However, the crop may present symptoms of toxicity, which may compromise plant development and reduce yield. Therefore, this work aimed to evaluate the response of 55 maize lines to the application of mesotrione and to study the genetic control linked to the tolerance of the lines to the herbicide. The experiments were conducted at the experimental unit of the company COODETEC in the Cascavel, in the agricultural year of 2014/15 and in the 2016. The experimental adopted was a randomized complete block design with three replications. The evaluated traits were carotenoid content, chlorophyll content and chlorophyll meter reading. The evaluations were made at the stages maize of development of V3 and V6. In the characterization experiment the symptoms presented by the plants were evaluated and 14 lines showed tolerance to the herbicide. Was observed genetic variability between strains for SPAD and carotenoid contents in the V3 and V6 stages. The CD11 and CD33 lines are indicated for studies on genetic control. The additive genetic factors are more important than the deviations of dominance, indicating the possibility of obtaining homozygous plants tolerant to the herbicide. The observed herdability estimates allow the achievement of satisfactory gains through selection.